2018
DOI: 10.1002/pbc.27072
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of splenectomy in pediatric hospitalizations with immune thrombocytopenia

Abstract: Overall, splenectomy rates consistently declined over time. Intracranial hemorrhage during hospitalizations with ITP was associated with occurrence of splenectomy. Future studies should continue to reevaluate the rates of splenectomy in pediatric ITP in the presence of various second-line pharmacologic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Providers enrolling in the ICON1 study reported that they chose splenectomy for its curative potential; however, very few were performed during the several years of this study . Splenectomy rates have been consistently declining over time with the increased use of pharmacologic therapies . Only four patients in this cohort underwent splenectomy during this study, consistent with this trend.…”
Section: Discussionsupporting
confidence: 57%
“…Providers enrolling in the ICON1 study reported that they chose splenectomy for its curative potential; however, very few were performed during the several years of this study . Splenectomy rates have been consistently declining over time with the increased use of pharmacologic therapies . Only four patients in this cohort underwent splenectomy during this study, consistent with this trend.…”
Section: Discussionsupporting
confidence: 57%
“…The NIS has been used to estimate population-level trends in numerous conditions. [15][16][17][18][19] Researchers and policymakers use the NIS to make national estimates of health care use, access, charges, quality, and outcomes. The NIS is released annually, which makes it an excellent database for longitudinal analysis.…”
Section: Methods Databasementioning
confidence: 99%
“…Hospitalizations with conditions which could be confounded with ITP were identified using relevant ICD-9/10-CM codes and excluded. Similar methodology has been used in past [14]. To eliminate double counting and improve completeness of data, transfers to skilled nursing facility (SNF), intermediate care facility (ICF), another type of facility, or to short-term facility were excluded using the "DISPUNIFORM" variable [15].…”
Section: Study Populationmentioning
confidence: 99%